Anti-cancer activity of m-carborane-containing trimethoxyphenyl derivatives through tubulin polymerization inhibition. Issue 6 (15th March 2019) - Kaise, Asako; Endo, Yasuyuki; Ohta, Kiminori
Graphical abstract: Abstract: m -Carborane-containing compound1a was identified as a cell growth inhibitor from a random screening of a boron compound library. As1a is a mixture of diastereomers due to the presence of two chiral carbons, we designed achiral derivatives2 –4 and studied the structure-activity relationships of the methoxy groups on the benzene ring. 3, 4, 5-Trimethoxybenzyl derivative2a and 3, 4, 5-trimethoxybenzoyl derivative3a showed more potent anti-cancer activity against the human breast cancer cell line MDA-MB-453 than lead compound1a . Compound3a inhibited tubulin polymerization in a dose-dependent manner.